Does Renewable Energy Matter to Achieve Sustainable Development Goals? The Impact of Renewable Energy Strategies on Sustainable Economic Growth - Chen, Jie; Su, Fan; Jain, Vipin; Salman, Asma; Tabash, Mosab I.; Haddad, Akram M.; Zabalawi, Eman; Abdalla, Alaa Amin; Shabbir, Malik Shahzad (Frontiers in Energy Research, 2022)
The influences of renewable and conventional energy consumption on ecological sustainability remain unclear because of the dynamic economic and innovative framework. This investigation gives a new perception by exploring the association between the production of various sources of renewable energies (e.g., hydroelectric, wind, solar PV, geothermal, and biomass power) and economic growth encapsulating capital, government spending, and trade openness. This research used a heterogeneous approach for panel data and second generational tools for econometrics, which allow for cross-sectional reliance and slope heterogeneity. This study has revealed the substantial reason to back up the feedback assumptions between renewable energy sources and economic growth, using the Dumitrescu and Hurlin analysis. In terms of policy, this empirical analysis suggests enacting impactful policies that encourage green power and economic reform in an attempt to lessen CO2 concentrations in the biosphere.